Mathematical Modelling of the Growth of Cajanus cajan in the Presence of Petroleum Oily Sludge Based on the Number of Shoots Produced - Allamin, Ibrahim Alkali; Ahmad, Siti Aqlima; Yasid, Nur Adeela; Abdullah, Siti Rozaimah Sheikh; Halmi, Mohd Izuan Effendi; Shukor, Mohd Yunus (Journal of Environmental Microbiology and Toxicology, 2018)
The use of Cajanus cajan (pigeon pea) or Kacang dhal in the phytoremediation of petroleum sludge in this study is novel. One of the challenges in monitoring the efficiency or inhibition of remediation by this toxic substance is measuring growth indicator. The number of shoots produced under growth on this toxic substance can be used to monitor the efficiency or inhibition and the use of mathematical models in describing the growth curve based on this parameter can give tangible results that can be used in further modelling exercise. In this study we demonstrated on the feasibility of using mathematical models in obtaining growth parameters based on the number of shoots produced under various concentrations of toxicants. The popular modified Gompertz growth model again prove itself as the best models in describing plant growth. The coefficients obtained in this study will be very valuable in secondary modelling exercise. This is the first time that mathematically modelling of the growth rate of C. cajan measured as the increase in number of shoots is carried out to the best of our knowledge.